'A Slight Degree of Tension': Training the Archaeologists of the Future. (September 2015) - Flatman, Joseph
Abstract : This paper stems from a presentation given at the University of Winchester in 2012 entitled 'Building People, Building Skills, Building Relationships and Building Jobs: Training the Archaeologists of the Future', which was part of the one-day conference '21st Century Archaeologists: Innovation in Training for Applied Archaeology'. Developing the content of that original presentation, but keeping its fundamental structure and argument, this paper reviews the pedagogical development of the academic discipline of archaeology in Britain from the post-war expansion of university-led archaeological training to the present day; consideration is not made, except in passing, to pre-degree training (e.g. in schools or further education colleges). Analysis of a range of sources demonstrates a surprising lack of formal pedagogy in archaeology as compared to other, comparable academic disciplines. Placed within the context of the broader development of the profession of archaeology, the reasons for this paucity of pedagogical development are discussed, alongside proposals for improvements in the future.